Total Quality Management in Academic Libraries: The Perception and Expectations of Graduate Students of The University of Ghana, Legon - Opoku, D. (Journal of Research in Education and Society, 2012)
This study focused on the perception and expectations of graduate students on Total Quality Management (TQM) in academic libraries with special reference to the University of Ghana Central Library (The Balme Library). The main theme of the study is the analysis of data in relation to service excellence, service effectiveness, service efficiency and continuous improvement in the Balme Library. This study used the quantitative survey method to generate data from 200 respondents out of the 450 total graduate population and the responses were analyzed using Krukal Wallis One-Way ANOVA (non-parametric) model to test the differences in perception and expectations of postgraduate users of the library. The study found out that in practical terms TQM is not being applied as a management technique in the Balme Library. It therefore concludes that the importance of TQM is not centered around postgraduate students' perception and expectations only, but also in anticipating and exceeding the demands of a fast changing environment of service delivery especially the academic libraries.
Research Article
Keywords: Total Quality Management; academic libraries; perception and expectations